Development of organic medium from agricultural by-product for cultivation of romaine lettuce - Theerak, Winakon; Atiganyanun, Sarun (Agriculture and Natural Resources, 2025)
Importance of the work: The development of an organic growth medium can promote sustainability in lettuce (Lactuca sativa L.) cultivation; however, costs remain an issue in developing countries. Objectives: To develop an optimal growth medium using compost from local organic sources for lettuce cultivation and to investigate the effects of heat treatment. Materials and Methods: Coir, charcoal, manure, soybean meal, molasses and rice bran were composted with fish bio-extract. The dry medium was produced via heating and regenerated using fish bio-extract. A completely randomized design was used for the lettuce growth experiment. The performance was evaluated of compost, dry and regenerated media and topsoil. Results: The compost medium had better nutrient profiles and microbial counts than common topsoil and commercial soil products, which led to improved lettuce growth. Heating the compost at 105°C significantly reduced the bulk density and the nitrogen content in the dry medium. The regeneration of the medium with the fish bio-extract increased the nitrogen content to the level of the compost medium and significantly restored the microorganism count. When used in romaine lettuce cultivation, the regenerated medium improved lettuce growth parameters, (plant height and width, fresh and dry weights) equal to those of the lettuce grown in the compost medium. Main finding: An accessible method was identified for producing inexpensive and an effective organic growth medium for lettuce cultivation. The heat treatment reduced the bulk density, microorganism count and nitrogen content; however, these could be restored via treatment with fish bio-extract.